Combined treatment by burosumab and a calcimimetic can ameliorate hypophosphatemia due to excessive actions of FGF23 and PTH in adult XLH with tertiary hyperparathyroidism: A case report - Takashi, Yuichi; Toyokawa, Kyoko; Oda, Naoki; Muta, Yoshimi; Yokomizo, Hisashi; Fukumoto, Seiji; Kawanami, Daiji (Frontiers in Endocrinology, 2022)
X-linked hypophosphatemia (XLH) is the most prevalent type of heritable fibroblast growth factor 23 (FGF23)-related hypophosphatemic rickets. Recently, anti-FGF23 antibody, burosumab, has become clinically available. We herein report a patient with adult XLH and tertiary hyperparathyroidism. The serum phosphate level and tubular maximum reabsorption of phosphate per glomerular filtration rate (TmP/GFR) remained low, despite burosumab treatment. While the influence of the relationship between FGF23 and parathyroid hormone (PTH) on the phosphaturic effect is unclear, it was considered that a high level of PTH due to tertiary hyperparathyroidism remains to suppress renal phosphate reabsorption. A calcimimetic, evocalcet, increased the serum phosphate level and TmP/GFR. Therefore, it is important to evaluate the presence of secondary-tertiary hyperparathyroidism in patients whose serum phosphate level does not increase with burosumab treatment.